Use of adjuvant and allelopathic plant extract to minimize the herbicide dose for controlling parthenium (Parthenium hysterophorus L.) in okra (Abelmoschus esculentus) - Safdar, Muhammad Ehsan; Mumtaz, Qaisar; Asif, Muhammad; Nadeem, Muhammad Ather; Ali, Amjed; Hussain, Sajad; Nadeem, Mubashar; Hayyat, Muhammad Sikander (Journal of Pure and Applied Agriculture, 2023)
Herbicide use in vegetables poses serious ecological and health hazards. To identify chemical strategy for minimizing herbicide doses with the use of adjuvant and allelopathic plant extract for controlling parthenium weed in okra, two-year field studies were undertaken at experimental area of College of Agriculture, University of Sargodha, Punjab-Pakistan during the summer seasons of years 2018 and 2019. The experimental treatments were a pre-emergence application of pendimethalin (495 g a.i. ha-1 ), post-emergence applications of metribuzin and halosulfuron at their full (518 g a.i. ha-1 and 37 g a.i. ha-1 , respectively) and 75% doses alone and tank-mixed application with alkyl ether sulfate (AES) adjuvant and aqueous extract of A. aspera (AAE). The results indicated that among two herbicides, the efficiency of halosulfuron was proved to be higher than metribuzin in terms of reducing parthenium dry weight and getting higher okra pod yield. Among two herbicides, halosulfuron showed greater enhancement in its efficacy by addition of adjuvant as compared to that shown by metribuzin. Halosulfuron full and 75% dose alone and in mixture with AES and AAE caused significantly the highest reduction in parthenium weed dry weight (up to 78%), while the highest increases in plant height (up to 76%), number of leaves (443%), number of pods (up to 256%), pod length (up to 66%) and pod yield (up to 82%) of okra in comparison to control. The reduced dose of halosulfuron in mixture with AES adjuvant showed the same performance as shown by its full dose alone in reducing weed density and dry weight and increasing pod yield of okra. It can be concluded that the halosulfuron dose can be reduced up to 25% if AES adjuvant was tank-mixed in it to obtain the same efficiency as with its full dose without compromising okra yield. © 2020 Department of Agricultural Sciences, AIOU